Evaluasi Strategi Fraud Prevention Dengan Menggunakan COSO Fraud Risk Management - Sidabutar, Harto Damedo; Julian, Lufti (Owner : Riset dan Jurnal Akuntansi, 2024)
The rise of corruption cases in Indonesia has an influence on the Indonesian Corruption Perception Index. Indonesia only got a score of 34 out of 100, a decrease of 4 points from the previous year which reached a score of 38, Indonesia was also ranked 110th out of 180 surveyed (TII, 2023). Fraud knows no place and can occur in any sector and agency, including entities that have duties and functions in enforcing the law and have fraud prevention mechanisms and systems that are documented in internal regulations and apply to the organization's people as a whole. This research aims to describe the implementation of fraud prevention strategies that currently exist in an entity and evaluate them based on a reference, namely the principles in the second edition of the Fraud Risk Management Guide (FRM Guide) published by COSO in 2023. The reference used is the latest in this research and also the research object, namely the Lembaga XYZ which is a government entity whose function is to carry out the mandate of the law. This research is a case study with an evaluation type, elaborating data analysis from interviews with questionnaires, as well as documentation data such as internal regulations and entity risk management reports. The sampling method was carried out with the author's justification for considering the representative organizational structure, the work unit of the technical organizer, and the characteristics of one unit and another with different functions. The research results show that the principles of Fraud Risk Management have been implemented quite well. However, the entity's fraud prevention strategy is still less effective because there is no specific intention to address the risk of fraud. The entity has not created a specific segregation of duties in managing fraud risk by a work unit and the fraud risk management program is still generally incorporated into the entity's risk management in general.